Effectiveness of estrogen in the prevention of intrauterine adhesions after hysteroscopic septal resection: A prospective, randomized study. Issue 4 (26th February 2014) - Roy, Kallol Kumar; Negi, Neha; Subbaiah, Murali; Kumar, Sunesh; Sharma, Jai Bhagwan; Singh, Neeta
Abstract Aim The aim of this prospective randomized study was to evaluate the efficacy of estrogen in preventing intrauterine adhesions following hysteroscopic septal resection and to investigate its effect on reproductive outcome. Materials and Methods After hysteroscopic septal resection, 90 women received either estrogen or placebo (n = 45 per group) for 30 days. A second‐look hysteroscopy was performed after 2 months. All pregnancies occurring during the study period were recorded. Results Adhesions developed in three of 43 (6.9%) patients in the control group compared to none in the estrogen group. This difference was not statistically significant (P = 0.24). Regarding reproductive outcome, the differences between the two groups were also not significant. Conclusion Estrogen treatment was not found to prevent intrauterine adhesions or improve reproductive outcome after hysteroscopic septal resection.